IMPLEMENTASI PELAYANAN ADMINISTRASI TERPADU KECAMATAN DI KANTOR KECAMATAN SAMARINDA ULU KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - Ismail Nurdin; Eka Ratna Amelia (Jurnal Media Birokrasi, 2019)
Entering the era of globalization the government realizes the importance of improving the quality and effectiveness of government administration services to meet the needs of society. Therefore, to meet these conditions, a policy has been formulated by the Central Government on Sub-District Integrated Administration Service, hereinafter in Indonesia abbreviated as PATEN. The purpose of this research was to determine and describe the process of implementation and the barriers that have occurred, as well as to know what efforts have been made in handling. In this research the writer use Implementation Theory by Edwards III which has four indicators; communication, resources, disposition, and bureaucratic structure. The research method used in this research is qualitative research, with descriptive method, through inductive approach. Technical data collection used is triangulation and as the instrument are observation, interview, and documentation. Based on the results observed by the writer, the implementation of PATEN in Samarinda Ulu sub-district has been implemented based on the prevailing provisions although still faced by various factors such as the limited budget and the ability of the implementing staff, the lack of service innovation, and there is still a lack of community understanding in the provisions of PATEN, so that the interests of citizens or communities associated with various types of licensing services and non-licensing have not all been served as expected. The advices given by the writer are to increase the operational budget as needed, carry out routine PATEN socialization, and hold a meeting session in giving new ideas in PATEN innovation. Keywords: Implementation, Public Service, Effectiveness.